Genetic diversity at four Nigerian sheep breeds assessed by variation of albumin and carbonic anhydrase in cellulose acetate electrophoretic systems (2018)
The aim of the study was to evaluate the occurrence and distribution of variations in blood protein markers in sheep breeds in Nigeria and to evaluate the relationships that exist among them. Atotal of 100 sheep comprising of twenty-five each of Balami, Uda, Yankassa and West African Dwarf (WAD) breeds were sampled for biochemical studies. Blood was collected to determine variations at the Albumin and Carbonic Anhydrase (CA) structural protein loci using F S A B cellulose acetate electrophoresis. All tested loci were polymorphic yielding four allelic variants (CA , CA , Alb , and Alb ) at the two protein loci. Genetic variability in the studied population was accessed using heterozygosity (observed – Ho and expected – He), effective number of alleles (Ne), fixation index (F) and gene flow (Nm). Genotypic frequencies ranged from 0.01 to 0.62 for CA and 0.25 to 0.49 for Alb loci. Estimated heterozygosity values ranged from 0.32±0.28 at Balami sheep to 0.70±0.22 in WAD with a global average estimated at 0.43±0.09 for all the breeds studied. The gene flow values for each of the loci studied were 0.82 and 1.24 for Alb and CA, respectively, with an average value of 1.03. The results showed that Yankassa and Balami sheep populations are more genetically (Nei's genetic identify value – 0.99) alike compared to Yankassa and WAD (0.73). Based on the values of heterozygosity (mean He =0.70 and Ho =0.45) assessed by variation of albumin and carbonic anhydrase the most genetic diverse is WAD sheep breed among the studied populations.